Expected and unexpected effects of sexism on women’s math performance - Smith Castro, Vanessa (2019)
Research has shown that gender differences in math performance are partially predicted by sociocultural aspects such as sexist ideologies and stereotypes. This study examined sexist ideologies as predictors of women’s performance in standardized math tests, and the mediation role of math-gender stereotypes and math self-efficacy on this relationship, while controlling for abstract reasoning. Data were analyzed in samples from High School girls and university women majoring in Social Sciences, Humanities and STEM. In secondary school, the results showed the indirect, albeit expected, effect of gender stereotypes on mathematical performance through mathematical self-efficacy. The model fit was lower at a university level, and an unexpectedly positive relationship emerged between hostile sexism and mathematical performance among STEM students. The results suggest several mechanisms by which gender ideologies and stereotypes affect women's mathematical performance.